LA / SA / PVA composite hydrogel, preparation method thereof and application of LA / SA / PVA composite hydrogel in treatment of blast furnace gas washing wastewater

Through the development and application of LA/SA/PVA composite hydrogel materials, the problems of difficulty and high cost of blast furnace gas washing water treatment are solved, and efficient COD removal and recycling are achieved to meet environmental protection requirements.

CN119236891APending Publication Date: 2025-01-03武汉钢铁有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411329604.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The blast furnace gas scrubber water treatment is difficult, high cost and low recycling rate. The existing adsorbents cannot meet the actual use requirements, especially it is difficult to effectively reduce COD content to achieve emissions according to standards.

Method used

Develop a LA/SA/PVA composite hydrogel material, and prepare a composite hydrogel with high adsorption properties and mechanical strength through the organic combination of sodium lignin sulfonate, sodium alginate and polyvinyl alcohol, and use it to The blast furnace gas washing water is adsorbed and its performance is improved through chemical modification and physical cross-linking methods.

Benefits of technology

The COD removal rate of blast furnace gas scrubber water has reached more than 70%, significantly reducing the pollutant content, meeting the emission requirements of standards, and the material can be recycled, energy-saving and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236891A_ABST
    Figure CN119236891A_ABST
Patent Text Reader

Abstract

The invention relates to LA / SA / PVA composite hydrogel, a preparation method thereof and application of the LA / SA / PVA composite hydrogel in treatment of blast furnace gas washing wastewater. The preparation method comprises the following steps: adding sodium alginate into a sodium lignin sulfonate solution to obtain an LA / SA solution, dropwise adding the LA / SA solution into a calcium chloride solution to obtain an LA / SA composite hydrogel, adding the LA / SA composite hydrogel into a glutaraldehyde solution, adding a polyvinyl alcohol solution for modification, filtering the mixture obtained by reaction, and freeze-drying to obtain the target product LA / SA / PVA composite hydrogel. According to the invention, the problems of poor adsorption effect, low mechanical strength and the like of single sodium alginate hydrogel are solved, and the composite hydrogel mainly comprising natural polymer organic matter sodium alginate and sodium lignin sulfonate coated polyvinyl alcohol is prepared through a physical cross-linking method and a chemical modification method. The composite hydrogel can be circularly used for deep treatment of blast furnace gas washing wastewater, is good in treatment effect and low in treatment cost, and has relatively good popularization and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogel materials and steel smelting wastewater treatment, and in particular to a LA / SA / PVA composite hydrogel and a preparation method thereof and application thereof in treating blast furnace gas washing wastewater. Background Art

[0002] Blast furnace gas washing water is a kind of wastewater produced in the process of cleaning and cooling blast furnace gas in the iron-making process. The composition of this wastewater is relatively complex. It not only contains a large amount of suspended matter, phenol cyanide, sulfide, inorganic salts and zinc metal ions, but also has high concentrations of COD, ammonia nitrogen and total nitrogen in the water. It has the characteristics of low B / C and high water temperature, and is difficult to treat.

[0003] There are many pollutants in the wastewater from blast furnace gas washing, which poses great environmental hazards. Therefore, environmental protection control is strict, requiring that it should not be discharged or discharged to a comprehensive sewage treatment station for further treatment. From the perspective of the circulating water system, if the wastewater is not discharged, salts will be seriously enriched, corrosion and scaling problems will be prominent, and it will be difficult to ensure water quality and quantity; from the perspective of the comprehensive sewage treatment station, conventional physical and chemical treatment processes have limited COD removal capabilities and no salt removal capabilities. The discharge of high-salt wastewater results in high conductivity and COD indicators of the effluent, making it difficult to reuse, which is extremely unfavorable for enterprises to reduce water pollutant emissions.

[0004] Focusing on the water quality and production maintenance and pollutant reduction issues of the blast furnace gas washing circulating water system, domestic and foreign technicians have carried out a series of research work and put forward relevant suggestions and measures. For example, appropriate sewage discharge combined with the addition of corrosion and scale inhibitors can solve the problem of water supply and production maintenance, and the pH value can be increased by adding alkali and a certain amount of sodium hypochlorite can be added to remove ammonia nitrogen, cyanide and high-valent metal ions in the sewage. However, there is no effective and applicable method to reduce the COD of sewage, which is still a topic worthy of in-depth research.

[0005] Looking at the current status of wastewater treatment technology at home and abroad, the methods for removing or degrading organic matter in wastewater include adsorption, chemical coagulation, electrochemical method, oxidation, biological method, micro-electrolysis, etc. Combined with the analysis of system water quality characteristics, site general conditions, investment and other engineering and technical conditions, the adsorption process is more suitable for COD treatment in blast furnace gas washing water system. However, the existing adsorbents cannot meet the actual use requirements, and it is urgent to develop a new adsorbent material to achieve the standard discharge of blast furnace gas washing water.

[0006] Sodium lignin sulfonate (LA) is a by-product of the papermaking industry. Its molecular structure contains aromatic phenolic hydroxyl groups, aliphatic hydroxyl groups and negatively charged groups (side chains), which can effectively adsorb dye molecules and organic matter in the solution. In addition, sodium lignin sulfonate also contains sulfonic acid functional groups, which give it good water solubility, dispersibility and surface activity. Using the unique structural characteristics of sodium lignin sulfonate, the natural biomass adsorbent developed has the advantages of being environmentally friendly and low-cost, and has been widely studied and applied in water treatment.

[0007] However, although pure lignin sulfonate exhibits certain adsorption properties, its own limited adsorption capacity has limited its application. Therefore, it is necessary to use the rich functional groups on the surface of lignin sulfonate to chemically modify and prepare lignin-based adsorption materials, so as to further enhance its adsorption performance. Currently common modification methods include phenolization, sulfonation, carboxymethylation, graft copolymerization and composite modification. To this end, we have developed a lignin-based sodium alginate / polyvinyl alcohol composite hydrogel material and its preparation method. Through the organic combination of lignin-based sodium sulfonate material and polyvinyl alcohol (PVA), the problems of poor adsorption effect and low mechanical strength of single sodium alginate (SA) hydrogel are effectively solved, and the adsorption performance and recovery performance of the composite material are significantly improved. Summary of the invention

[0008] The purpose of the present invention is to solve the problems of great difficulty in treating existing blast furnace gas washing water, high treatment cost, and low recycling rate. A new type of composite hydrogel material has been developed and used to treat blast furnace gas washing water. Not only does it reduce the COD and pollutant content in the wastewater to achieve standard discharge, but the composite hydrogel material can also be recycled, which helps to save energy and protect the environment.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] A method for preparing a LA / SA / PVA composite hydrogel comprises: preparing a LA / SA solution by using sodium alginate and sodium lignin sulfonate; mixing the LA / SA solution with a calcium chloride solution to obtain a LA / SA composite hydrogel; mixing the LA / SA composite hydrogel with an aldehyde solution (such as glutaraldehyde), and then adding a polyvinyl alcohol solution to finally obtain a LA / SA / PVA composite hydrogel.

[0011] Furthermore, the preparation process of LA / SA solution is as follows: sodium lignin sulfonate is dissolved in deionized water at 20-40° C., and then sodium alginate is added and dispersed evenly by stirring, ultrasound or the like.

[0012] Furthermore, the concentration of sodium alginate in the LA / SA solution is 50-110 g / L, and the concentration of sodium lignin sulfonate is 10-20 g / L.

[0013] Furthermore, the LA / SA solution was added dropwise into the calcium chloride solution at 20-40° C. and a rotation speed of 40-80 r / min to prepare the LA / SA composite hydrogel.

[0014] Furthermore, the volume ratio of the LA / SA solution and the calcium chloride solution when mixed is 1:3-9.

[0015] Furthermore, the concentration of the calcium chloride solution is 2wt%-8wt%.

[0016] Furthermore, at 40-60° C. and a rotation speed of 150-250 r / min, the LA / SA composite hydrogel is added to a glutaraldehyde solution, and then a polyvinyl alcohol solution is added, and the resulting mixture is fully stirred for reaction to obtain a LA / SA / PVA composite hydrogel.

[0017] Furthermore, the concentration of the glutaraldehyde solution is 0.1 wt%-2 wt%, and the amount added is equivalent to 2-8 times the volume of the LA / SA solution.

[0018] Furthermore, the concentration of the polyvinyl alcohol solution is 10-30 g / L, and the amount added is equivalent to 1-2 times the volume of the LA / SA solution.

[0019] Furthermore, after the reaction, the LA / SA / PVA composite hydrogel is obtained by centrifugation or filtration, and after washing, it is placed in a -10 to -30°C environment for pre-freezing for 16-30 hours, and then transferred to a -30 to -60°C environment for continued vacuum freezing for 16-30 hours, thereby obtaining a dry LA / SA / PVA composite hydrogel. Freeze drying can make the hydrogel loose and porous with almost unchanged volume, and it is easy to store for a long time. Considering the thoroughness of dehydration and economic cost, the freeze drying time is preferably set to about 24 hours.

[0020] The second object of the present invention is to provide a LA / SA / PVA composite hydrogel prepared according to the above method.

[0021] The third purpose of the present invention is to facilitate the above-mentioned LA / SA / PVA composite hydrogel to treat blast furnace gas washing water. The specific process is as follows: adding regenerated or new LA / SA / PVA composite hydrogel to blast furnace gas washing water for adsorption, obtaining old composite hydrogel and treated washing water after solid-liquid separation, and regenerating the old composite hydrogel and adding it back to blast furnace gas washing water for adsorption treatment.

[0022] Furthermore, the pH of the blast furnace gas washing water before treatment is 7, and the COD value is 150-300 mg / L.

[0023] Furthermore, the addition amount of LA / SA / PVA composite hydrogel is 0.1-5 g / L blast furnace gas washing water, and the adsorption temperature is 15-30°C.

[0024] Furthermore, the regeneration method of the old composite hydrogel is as follows: the old composite hydrogel is added into a HNO3 aqueous solution (0.1 mol / L), fully immersed in an ultrasonic environment for desorption, then the composite hydrogel is taken out and repeatedly rinsed with deionized water until the washing solution is neutral, and finally freeze-dried for use.

[0025] The present invention uses sodium lignin sulfonate and sodium alginate as raw materials for producing hydrogel, ensuring that the prepared hydrogel is easy to degrade and has low cost. The increase in the amount of sodium alginate can increase the content of carboxyl functional groups. Based on the coordination adsorption mechanism between carboxyl groups and pollutants, the increase in carboxyl content can potentially improve the adsorption efficiency of LA / SA / PVA composite hydrogel on organic matter in blast furnace gas washing water.

[0026] When the LA / SA composite hydrogel is prepared by the present invention, the addition of CaCl2 is conducive to the formation of a three-dimensional network inside the sodium alginate hydrogel, so that the adsorption performance of the final product is significantly enhanced. If the amount of CaCl2 is too little, less free radicals will be generated, which is not conducive to the subsequent polymerization and cross-linking reactions; if the amount of CaCl2 is too much, too many free radicals will be generated in the reaction system, resulting in a decrease in the average kinetic chain length of the polymer, too small molecular weight between the cross-linking points of the polymer, and poor adsorption performance of the resulting hydrogel. Therefore, the amount of CaCl2 added must be controlled within a reasonable and appropriate range.

[0027] The present invention blends polyvinyl alcohol with LA / SA composite solution to form a composite hydrogel, which can not only improve the relatively poor mechanical stability of the original sodium alginate hydrogel, making the solid-liquid separation and regeneration of the hydrogel after adsorbing pollutants simple, but also increase the number of -OH functional groups on the composite hydrogel, thereby enhancing the adsorption efficiency of the composite hydrogel for pollutants.

[0028] The addition of cross-linking agent glutaraldehyde forms an interpenetrating network structure between sodium alginate and polyvinyl alcohol. As the amount of cross-linking agent increases, the cross-linking degree of the composite hydrogel gradually increases, causing its structure to become loose. The loose pore structure can give the hydrogel a larger specific surface area, providing sufficient binding sites for the adsorption of organic matter in the later stage. However, when the concentration of the cross-linking agent glutaraldehyde exceeds 2wt%, the cross-linking degree between the macromolecular chains of the composite hydrogel becomes too high, the relaxation of the internal network of the hydrogel is destroyed, and it is difficult for pollutants to enter the interior of the hydrogel from the surface, which means that the swelling degree of the hydrogel becomes smaller and the adsorption performance becomes worse.

[0029] Compared with existing similar products or technologies, the beneficial effects of the present invention are embodied in the following aspects: (1) The present invention uses sodium alginate as the hydrogel matrix, and forms a hydrogel by physical crosslinking and chemical modification with sodium lignin sulfonate and polyvinyl alcohol, which not only enriches the surface functional groups of the hydrogel material, but also gives it a larger specific surface area, thereby effectively improving the adsorption capacity of the hydrogel material. The modification also improves the mechanical strength of the single sodium alginate hydrogel, which is beneficial to solid-liquid separation and recycling; (2) The LA / SA / PVA composite hydrogel prepared by the present invention has excellent performance and can be used to treat blast furnace gas washing wastewater with a high COD content, with a removal rate of more than 70%, and has good application prospects in the deep treatment of blast furnace gas washing wastewater; (3) The preparation method of the LA / SA / PVA composite hydrogel of the present invention is simple, the reaction conditions are simple and easy, and the sodium lignin sulfonate and sodium alginate in the raw materials are widely available. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the SEM image of the LA / SA / PVA composite hydrogel prepared in Example 1.

[0031] Figure 2 This is the SEM image of the unmodified single SA hydrogel prepared in Comparative Example 1.

[0032] Figure 3 This is the FTIR image of the LA / SA / PVA composite hydrogel prepared in Example 1.

[0033] Figure 4 This is a comparison chart of the COD removal effects of the LA / SA / PVA composite hydrogel prepared in Example 1 and the unmodified single SA hydrogel prepared in Comparative Example 1.

[0034] Figure 5 This is a time-COD removal rate relationship diagram of the LA / SA / PVA composite hydrogel prepared in Example 1. DETAILED DESCRIPTION

[0035] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, the following is further described in conjunction with specific embodiments and drawings. It should be noted that the following embodiments are only preferred implementations of the present invention, not all of the present invention, and other simple improvements based on the concept of the present invention still fall within the scope of protection of the present invention.

[0036] Example 1

[0037] (1) 2.0 g of polyvinyl alcohol was weighed using an analytical balance and poured into a beaker. 100 mL of deionized water was then added. The resulting mixture was heated to 90° C. and stirred at 200 r / min for 30 min. After the polyvinyl alcohol was completely dissolved, a clear and transparent polyvinyl alcohol solution (concentration = 20 g / L) was obtained.

[0038] 1.0 g of sodium lignin sulfonate powder was weighed with an analytical balance and poured into a beaker, and 60 mL of deionized water was added. The resulting mixture was heated to 25° C. and stirred for 20 min. After the sodium lignin sulfonate was completely dissolved, a yellow-brown sodium lignin sulfonate solution (concentration = 16.7 g / L) was obtained.

[0039] (2) Weigh 5.0 g of sodium alginate using an analytical balance, add the weighed sodium alginate to the above sodium lignin sulfonate solution at 25°C and 200 r / min, and mix by ultrasonic for 1 h to obtain a uniform and viscous sodium lignin sulfonate / sodium alginate solution. The concentration of sodium alginate in the sodium lignin sulfonate / sodium alginate solution is 83.3 g / L.

[0040] (3) At 30°C and 60 r / min, the sodium lignin sulfonate / sodium alginate solution was uniformly added dropwise to 300 mL of a 5 wt% calcium chloride aqueous solution to obtain a hydrogel. After the addition was completed, the mixture was immersed for 12 h at this temperature and speed to further gel the hydrogel.

[0041] (4) LA / SA composite hydrogel was separated from the mixture, and then added into 200 mL of 1 wt% glutaraldehyde aqueous solution, and then the prepared polyvinyl alcohol solution was added. The resulting mixture was heated to 50°C and stirred at 200 r / min for 12 h. After centrifugation, the LA / SA / PVA wet gel was separated by filtration.

[0042] (5) RO water and anhydrous ethanol were used to wash away impurities on the surface of the LA / SA / PVA wet gel, respectively. After washing, the wet gel was placed in a refrigerator and pre-frozen at -18°C for 24 h. After pre-freezing, the wet gel was transferred to a vacuum freeze dryer and freeze-dried at -50°C for 24 h to finally obtain the LA / SA / PVA composite hydrogel.

[0043] Comparative Example 1

[0044] (1) 5.0 g of sodium alginate was weighed using an analytical balance and poured into a beaker. 60 mL of deionized water was then added. The resulting mixture was heated to 25° C. and stirred at 200 r / min for 30 min. After the addition was completed, ultrasonic mixing was performed for 1 h to obtain a sodium alginate solution with a concentration of 83.3 g / L.

[0045] (2) At 30°C and 60 r / min, the sodium alginate solution was uniformly added dropwise to 300 mL of a 5 wt% calcium chloride aqueous solution to obtain a hydrogel. After the addition was completed, the mixture was immersed for 12 h at this temperature and speed to further gel the hydrogel.

[0046] (3) SA wet gel was separated from the mixture, and impurities on the surface of the SA wet gel were washed away with RO water and anhydrous ethanol respectively. After washing, the wet gel was transferred to a refrigerator and pre-frozen at -18°C for 24 hours. After pre-freezing, the wet gel was placed in a vacuum freeze dryer and freeze-dried at -50°C for 24 hours to finally obtain an unmodified single SA hydrogel.

[0047] In order to fully understand the various properties of the two hydrogels prepared in Example 1 and Comparative Example 1, samples were taken and corresponding tests were performed, as follows:

[0048] (1) Scanning electron microscope analysis test (SEM)

[0049] The hydrogel products obtained in Example 1 and Comparative Example 1 were subjected to SEM tests, and the results were as follows: Figure 1-2 As shown. Figure 1 It can be seen that the LA / SA / PVA composite hydrogel has an obvious and compact pore structure; at the same time, Figure 2 It can be seen that the surface of the untreated single SA hydrogel is smooth and has almost no pore structure. This shows that through the connection of the crosslinker GA, the hydroxyl bonding of LA, SA and PVA increases the spatial structure and specific surface area of ​​the LA / SA / PVA composite hydrogel, making its surface rich in pores, thus exposing more binding sites.

[0050] (2) Infrared spectroscopy test (FTIR)

[0051] A small amount of LA / SA / PVA composite hydrogel prepared in Example 1 was tested by infrared spectroscopy. The results are as follows: Figure 3 As shown. Figure 3 As can be seen, 1608cm -1 The absorption peak at 3375cm corresponds to the stretching vibration of the CO bond in SA, which indicates that the hydrogel surface contains -COOH; -1 The characteristic peak at corresponds to -OH, which is broad and intense, indicating that the modification of PVA increases the number of -OH functional groups in the composite hydrogel and that hydrogen bonds may form between molecules, which also confirms the successful modification of PVA. In summary, LA / SA / PVA composite hydrogels with functional groups -COOH and -OH on the surface were successfully synthesized through physical cross-linking reaction and chemical modification.

[0052] (3) Control experiment of using hydrogel to treat blast furnace gas washing wastewater

[0053] Take a portion of the biologically treated blast furnace gas washing wastewater sample at the outlet, adjust its pH to 7, and then test the COD value of the wastewater with reference to the potassium chromate method in the national standard (GB / T 11914-2022). With an addition amount of 1.0g hydrogel / L of wastewater, the LA / SA / PVA composite hydrogel prepared in Example 1 and the unmodified single SA hydrogel prepared in Comparative Example 1 were added to a conical flask containing 50mL of blast furnace gas washing water, and the resulting mixture was placed under constant temperature oscillation adsorption at 25°C for 3h (sampling and testing were performed every hour during this period). After filtration, the treated wastewater was collected and its COD was determined. The COD removal rate of the hydrogel was calculated according to the formula (COD removal rate = (COD before treatment-COD after treatment) / COD before treatment) to determine the adsorption performance of different hydrogels. The test results are shown in Tables 1 and 2 below. Figure 4 shown.

[0054] Table 1 Comparison of wastewater COD removal effects of different hydrogels

[0055]

[0056] As can be seen from the table above, the COD removal rate of the LA / SA / PVA composite hydrogel is much greater than that of the single SA hydrogel. This proves that the LA / SA / PVA hydrogel prepared in Example 1 exhibits a higher adsorption capacity, and also proves that we have successfully synthesized a LA / SA / PVA composite hydrogel with a higher adsorption capacity.

[0057] (4) Experiment on the relationship between time and removal rate of blast furnace gas washing wastewater treatment

[0058] Referring to the control test of (3), the LA / SA / PVA composite hydrogel prepared in Example 1 was added to a conical flask containing 50 mL of blast furnace gas washing water, and the resulting mixture was placed in a constant temperature oscillation adsorption environment at 25°C for 1 h, 2 h, 3 h, 4 h, and 5 h. After filtration, the treated wastewater was collected and its COD was determined. The COD removal rate of the hydrogel under different adsorption treatment times was calculated. The test results are shown in Tables 2 and 3. Figure 5 shown.

[0059] Table 2 Results of wastewater COD removal rate at different adsorption times

[0060]

[0061] As can be seen from the table above, the hydrogel adsorbs COD very quickly within the first 4 hours, and then the adsorption rate gradually increases until it reaches equilibrium. The initial adsorption may be due to the presence of abundant active sites on the surface of the LA / SA / PVA hydrogel, which facilitates contact with pollutants; after 4 hours, as the adsorption process proceeds, the available active sites on the LA / SA / PVA hydrogel become limited, and there are not enough active sites to bind more pollutants, resulting in a slowdown in the removal efficiency of COD. Taking all factors into consideration, 5 hours was selected as the optimal adsorption time for LA / SA / PVA hydrogel.

[0062] In addition, the table also shows that the COD removal rate of the LA / SA / PVA composite hydrogel prepared in Example 1 of the present invention for blast furnace gas washing water can reach up to 70% or more. Under the condition that the raw water COD is 150 mg / L, the effluent meets the national standard (GB13456-2012, Table 2) emission requirement of COD ≤ 50 mg / L.

[0063] (5) Regeneration cycle adsorption experiment of LA / SA / PVA composite hydrogel

[0064] The LA / SA / PVA composite hydrogel prepared in Example 1 was added to a conical flask containing 50 mL of blast furnace gas washing water, and the resulting mixture was placed in a constant temperature oscillation adsorption environment at 25°C for 5 hours. After filtration, the treated wastewater was collected and its COD was determined. The filtered LA / SA / PVA hydrogel was regenerated according to the following method: 0.1 mol / L HNO3 solution was used as a desorbent, and the adsorbed LA / SA / PVA composite hydrogel was added under an ultrasonic environment for desorption, and then the LA / SA / PVA composite hydrogel was repeatedly rinsed with deionized water for more than 3 times until the washing solution was neutral, and the washed wet LA / SA / PVA composite hydrogel was freeze-dried for use.

[0065] Referring to the above method, the regenerated LA / SA / PVA composite hydrogel was used to re-adsorb and treat the blast furnace gas washing water. After 5 cycles of adsorption-regeneration, the measured COD removal rate is shown in Table 3 below.

[0066] Table 3 Relationship between the number of LA / SA / PVA composite hydrogel cycle regeneration times and wastewater COD removal rate

[0067]

[0068] It can be seen from the above table that after 5 cycles of regeneration, the LA / SA / PVA hydrogel adsorbent still maintains the removal effect on the COD of the washing water, and after 2 cycles of adsorption regeneration, the adsorption removal rate of COD by the LA / SA / PVA hydrogel can still reach more than 60%, which shows that the LA / SA / PVA composite hydrogel has good reusability.

[0069] Example 2

[0070] (1) 1.5 g of polyvinyl alcohol was weighed using an analytical balance and poured into a beaker. 100 mL of deionized water was then added. The resulting mixture was heated to 80° C. and stirred at 200 r / min for 40 min. After the polyvinyl alcohol was completely dissolved, a clear and transparent polyvinyl alcohol solution (concentration = 15 g / L) was obtained.

[0071] 0.8 g of sodium lignin sulfonate powder was weighed with an analytical balance and poured into a beaker, and 60 mL of deionized water was added. The resulting mixture was heated to 30° C. and stirred for 25 min. After the sodium lignin sulfonate was completely dissolved, a yellow-brown sodium lignin sulfonate solution (concentration = 13.36 g / L) was obtained.

[0072] (2) Weigh 6.0 g of sodium alginate using an analytical balance, add the weighed sodium alginate to the above sodium lignin sulfonate solution at 30° C. and a rotation speed of 200 r / min, and ultrasonically mix for 2 h to obtain a uniform and viscous sodium lignin sulfonate / sodium alginate solution. The concentration of sodium alginate in the sodium lignin sulfonate / sodium alginate solution is 100.2 g / L.

[0073] (3) At 25°C and 65 r / min, the sodium lignin sulfonate / sodium alginate solution was uniformly added dropwise to 250 mL of a 3 wt% calcium chloride aqueous solution to obtain a hydrogel. After the addition was completed, the mixture was immersed for 12 h at this temperature and speed to further gel the hydrogel.

[0074] (4) LA / SA composite hydrogel was separated from the mixture, and then added into 400 mL of 0.6 wt% glutaraldehyde aqueous solution, and then added with the prepared polyvinyl alcohol solution. The resulting mixture was heated to 60°C and stirred at 180 r / min for 16 h. After centrifugation, the LA / SA / PVA wet gel was separated by filtration.

[0075] (5) RO water and anhydrous ethanol were used to wash away impurities on the surface of the LA / SA / PVA wet gel, respectively. After washing, the wet gel was transferred to a refrigerator and pre-frozen at -20°C for 20 h. After pre-freezing, the wet gel was placed in a vacuum freeze dryer and freeze-dried at -60°C for 18 h to finally obtain the LA / SA / PVA composite hydrogel.

[0076] Example 3

[0077] (1) 2.5 g of polyvinyl alcohol was weighed using an analytical balance and poured into a beaker. 100 mL of deionized water was then added. The resulting mixture was heated to 85° C. and stirred at 200 r / min for 35 min. After the polyvinyl alcohol was completely dissolved, a clear and transparent polyvinyl alcohol solution (concentration = 25 g / L) was obtained.

[0078] 0.9 g of sodium lignin sulfonate powder was weighed with an analytical balance and poured into a beaker, and 70 mL of deionized water was added. The resulting mixture was heated to 35° C. and stirred for 30 min. After the sodium lignin sulfonate was completely dissolved, a yellow-brown sodium lignin sulfonate solution (concentration = 12.86 g / L) was obtained.

[0079] (2) Weigh 5.25 g of sodium alginate using an analytical balance, add the weighed sodium alginate to the above sodium lignin sulfonate solution at 35°C and 200 r / min, and mix by ultrasonic for 1.25 h to obtain a uniform and viscous sodium lignin sulfonate / sodium alginate solution. The concentration of sodium alginate in the sodium lignin sulfonate / sodium alginate solution is 75 g / L.

[0080] (3) At 35°C and 70 r / min, the sodium lignin sulfonate / sodium alginate solution was uniformly added dropwise to 350 mL of a 4 wt% calcium chloride aqueous solution to obtain a hydrogel. After the addition was completed, the mixture was immersed for 18 h at this temperature and speed to further gel the hydrogel.

[0081] (4) LA / SA composite hydrogel was separated from the mixture, and then added into 250 mL of 0.8 wt% glutaraldehyde aqueous solution, and then added with the prepared polyvinyl alcohol solution. The resulting mixture was heated to 55°C and stirred at 190 r / min for 15 h. After centrifugation, the LA / SA / PVA wet gel was separated by filtration.

[0082] (5) RO water and anhydrous ethanol were used to wash away impurities on the surface of the LA / SA / PVA wet gel, respectively. After washing, the wet gel was transferred to a refrigerator and pre-frozen at -22°C for 22 h. After pre-freezing, the wet gel was placed in a vacuum freeze dryer and freeze-dried at -55°C for 20 h to finally obtain the LA / SA / PVA composite hydrogel.

[0083] Example 4

[0084] (1) 3.0 g of polyvinyl alcohol was weighed using an analytical balance and poured into a beaker. 100 mL of deionized water was then added. The resulting mixture was heated to 95° C. and stirred at 200 r / min for 25 min. After the polyvinyl alcohol was completely dissolved, a clear and transparent polyvinyl alcohol solution (concentration = 30 g / L) was obtained.

[0085] 0.85 g of sodium lignin sulfonate powder was weighed with an analytical balance and poured into a beaker, and 65 mL of deionized water was added. The resulting mixture was heated to 40° C. and stirred for 25 min. After the sodium lignin sulfonate was completely dissolved, a yellow-brown sodium lignin sulfonate solution (concentration = 13.08 g / L) was obtained.

[0086] (2) Weigh 5.5 g of sodium alginate using an analytical balance, add the weighed sodium alginate to the above sodium lignin sulfonate solution at 40°C and 200 r / min, and mix by ultrasonic for 1.5 h to obtain a uniform and viscous sodium lignin sulfonate / sodium alginate solution. The concentration of sodium alginate in the sodium lignin sulfonate / sodium alginate solution is 84.6 g / L.

[0087] (3) At 40°C and 75 r / min, the sodium lignin sulfonate / sodium alginate solution was uniformly added dropwise to 400 mL of a 6 wt% calcium chloride aqueous solution to obtain a hydrogel. After the addition was completed, the mixture was immersed for 16 h at this temperature and speed to further gel the hydrogel.

[0088] (4) LA / SA composite hydrogel was separated from the mixture, and then added into 300 mL of 1.2 wt% glutaraldehyde aqueous solution, and then added with the prepared polyvinyl alcohol solution. The resulting mixture was heated to 45°C and stirred at 220 r / min for 16 h. After centrifugation, the LA / SA / PVA wet gel was separated by filtration.

[0089] (5) RO water and anhydrous ethanol were used to wash away impurities on the surface of the LA / SA / PVA wet gel, respectively. After washing, the wet gel was transferred to a refrigerator and pre-frozen at -25°C for 22 h. After pre-freezing, the wet gel was placed in a vacuum freeze dryer and freeze-dried at -52°C for 18 h to finally obtain the LA / SA / PVA composite hydrogel.

Claims

1. A method for preparing a LA / SA / PVA composite hydrogel, characterized in that The method comprises: preparing LA / SA solution by using sodium alginate and sodium lignin sulfonate; mixing the LA / SA solution with a calcium chloride solution to obtain a LA / SA composite hydrogel; mixing the LA / SA composite hydrogel with an aldehyde solution, adding a polyvinyl alcohol solution, and reacting to obtain a LA / SA / PVA composite hydrogel.

2. The method according to claim 1, characterized in that The preparation process of LA / SA solution is as follows: sodium lignin sulfonate is dissolved in deionized water at 20-40° C., and sodium alginate is added and dispersed evenly.

3. The method according to claim 1, characterized in that: At 20-40° C. and a rotation speed of 40-80 r / min, the LA / SA solution was added dropwise to the calcium chloride solution in a volume ratio of 1:3-9 to prepare the LA / SA composite hydrogel.

4. The method according to claim 1, characterized in that: At 40-60° C. and a rotation speed of 150-250 r / min, the LA / SA composite hydrogel is added to a glutaraldehyde solution with a volume of 2-8 times that of the LA / SA solution, and then a polyvinyl alcohol solution with a volume of 1-2 times that of the LA / SA solution is added, and the resulting mixture is fully stirred to react to obtain a LA / SA / PVA composite hydrogel.

5. The method according to claim 1, characterized in that: After the reaction, the separated LA / SA / PVA composite hydrogel was first washed thoroughly, and then placed in a -10 to -30°C environment for pre-freezing for 16 to 30 hours, and then transferred to a -30 to -60°C environment for continued vacuum freezing for 16 to 30 hours.

6. The method according to claim 1, characterized in that: The concentration of sodium alginate in the LA / SA solution is 50-110 g / L, the concentration of sodium lignin sulfonate is 10-20 g / L, the concentration of calcium chloride solution is 2wt%-8wt%, the concentration of aldehyde solution is 0.1wt%-2wt%, and the concentration of polyvinyl alcohol solution is 10-30 g / L.

7. A LA / SA / PVA composite hydrogel, characterized in that: The composite hydrogel is prepared according to any one of the methods of claims 1 to 6, and has a rich pore structure on its surface.

8. Use of the LA / SA / PVA composite hydrogel according to claim 7 in treating blast furnace gas washing water.

9. The use according to claim 8, characterized in that The specific process of this application is as follows: adding regenerated or new LA / SA / PVA composite hydrogel to blast furnace gas washing water for adsorption, solid-liquid separation to obtain old composite hydrogel and treated washing water, and regenerating the old composite hydrogel and adding it back to blast furnace gas washing water for adsorption.

10. The use according to claim 9, characterized in that: The pH of blast furnace gas washing water before treatment is 7, and the COD value is 150-300 mg / L; the addition amount of LA / SA / PVA composite hydrogel is 0.1-5 g / L blast furnace gas washing water, and the adsorption temperature is 15-30°C; the regeneration method of the old composite hydrogel is: add the old composite hydrogel to HNO3 aqueous solution for ultrasonic immersion desorption, then take out the composite hydrogel and wash it with deionized water until neutral, and finally freeze-dry it for use.

Citation Information

Cited By

  • Preparation method of hydrophobic modified alginate

    CN122230687A